ANALYSIS OF GROWTH OF LALAWAK Barbonymus balleroides (VALENCIENNES, 1842) IN THREE CULTURE METHODS - Deni Radona; Vitas Atmadi Prakoso; Irin Iriana Kusmini (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
In fish culture, optimal growth could be influenced by various culture methods. Aim of the study was to evaluate the productivity of Barbonymus balleroides, lalawak in floating net cages, concrete ponds, and earthen ponds. Cultivation was designed with the circulation water system. Experiment was conducted using completely randomized design with three treatments and three replications for each treatment. The experimental fish, sized of 4.20 ± 0.64 cm SL and weight of 2.14 ± 0.99 g, were obtained from induced breeding. The stocking density used was 20 individuals/m3. Fish were fed 3% of total weight two times every day using commercial pellet with 35% protein content for 90 day. The result showed that lalawak reared in earthen pond was no significant difference on length, weight, and biomass compared with that one in concrete pond (P>0.05), but significantly different (P<0.05) with floating net cages. There were no different (P>0.05) among the three different culture systems for survival rate and FCR. Lalawak reared on earthen pond system supported with optimal water quality could increase productivity value.